Preparation method and application of superhard wear-resistant antifouling composite coating
By using organic-inorganic hybrid technology to construct a "hard and flexible" coating network, the wear resistance and adhesion problems of existing coatings are solved, and a high-hardness, wear-resistant and low-cost anti-fouling composite coating is achieved, which is suitable for architectural decoration, electronic equipment and machinery manufacturing.
Patent Information
- Application Number
- CN202511094467.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-06
- Publication Date
- 2025-09-09
- Estimated Expiration
- 2045-08-06
AI Technical Summary
Existing superhard and wear-resistant coating materials have problems such as insufficient wear resistance, poor adhesion, high cost, complex process and environmental risks.
By adopting organic-inorganic hybrid technology, through coupling agent, nanoparticle dispersion, PETA cross-linking and silicone oil flexible adjustment, a 'rigid and flexible' organic-inorganic hybrid network is constructed to prepare an ultra-hard, wear-resistant and anti-fouling composite coating.
The result is a high-hardness, wear-resistant, scratch-resistant and low-cost coating suitable for multiple high-value-added fields with good mechanical strength and anti-fouling properties.
Smart Images

Figure CN120607860A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of coating materials, and in particular to a preparation method and application of a super-hard, wear-resistant and anti-fouling composite coating. Background Art
[0002] Existing ultra-hard, scratch-resistant, and wear-resistant coating technologies are widely used in multiple fields, including industrial manufacturing, aerospace, the automotive industry, and consumer electronics. However, current technologies often use a single organic or inorganic material, which generally suffers from problems such as insufficient wear resistance, poor adhesion, toxicity to the human body, or complex construction. For example, traditional organic coatings (such as polyurethane) are prone to aging, while inorganic coatings (such as silica) are brittle and prone to peeling. Although there are studies to improve performance through organic-inorganic hybrid technology, they generally suffer from drawbacks such as high cost, poor weather resistance, or complex processes. In addition, materials such as rigid polyurethane foam are flammable and require the addition of flame retardants, but existing flame-retardant coatings often contain halogens or heavy metals, posing environmental risks. Therefore, the development of an ultra-hard, wear-resistant, and high-performance organic-inorganic hybrid coating is of great significance. Summary of the Invention
[0003] The purpose of the present invention is to provide a preparation method and application of a superhard wear-resistant and antifouling composite coating, wherein the coating has good wear resistance.
[0004] To achieve the above object, the present invention provides a superhard wear-resistant antifouling composite coating, comprising
[0005] 30-80 parts by weight of coupling agent
[0006] 3-10 parts by weight of deionized water
[0007] 100-300 parts by weight of anhydrous ethanol
[0008] 5-50 parts by weight of amino silicone oil
[0009] 1-30 parts by weight of hydroxy silicone oil
[0010] 1-20 parts by weight of glycerol
[0011] Pentaerythritol triacrylate 200-500 parts by weight
[0012] Propylene glycol methyl ether acetate 50-200 parts by weight
[0013] 20-200 parts by weight of nanoparticle dispersion.
[0014] Preferably, the mass ratio of hydroxy silicone oil, amino silicone oil and glycerol is 3:5:2; The mass ratio of pentaerythritol triacrylate, anhydrous ethanol and propylene glycol methyl ether acetate is 3:1:1.
[0015] Preferably, the coupling agent is one or more of a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, and a zirconate coupling agent.
[0016] Preferably, the coupling agent is one or more of γ-aminopropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltriethoxysilane, tetrabutyl titanate, bis(ethyl acetoacetate)di-n-butoxy titanate, aluminum triacetylacetonate, (ethyl acetoacetate)diisopropoxyaluminate, tetrakis(triethanolamine)zirconium, and alkoxytris(p-aminophenoxy)zirconate.
[0017] Preferably, the nanoparticle dispersion is one of zirconium oxide, aluminum oxide, titanium oxide and silicon oxide.
[0018] A method for preparing a superhard, wear-resistant, and antifouling composite coating comprises the following steps: Preparation of coupling agent hydrolyzate: Mix the coupling agent and anhydrous ethanol in proportion, add deionized water, place in a constant temperature water bath and stir to obtain coupling agent hydrolyzate; Preparation of Liquid A: Mix hydroxy silicone oil, amino silicone oil and glycerol and stir to form a uniform mixture of Liquid A; Preparation of nanoparticle dispersion: dispersing nanoparticles in an aqueous solution to prepare a nanoparticle dispersion; Preparation of Liquid B: Pentaerythritol triacrylate, anhydrous ethanol and propylene glycol methyl ether acetate were mixed and stirred to form a uniform mixture of Liquid B; Preparation of mixed emulsion: slowly add liquid A to liquid B and mix evenly, stir, slowly add coupling agent hydrolyzate and stir, and finally slowly add nanoparticle dispersion and continue stirring to obtain a uniform mixed emulsion; Coating curing: The mixed emulsion is applied to the surface of the pretreated substrate and cured to obtain a coating.
[0019] Preferably, the substrate comprises glass, metal, wood or ceramic.
[0020] Preferably, in the step of preparing the coupling agent hydrolyzate, a mixed solution of the coupling agent and deionized water is prepared, wherein the deionized water accounts for 10% of the mass of the coupling agent, and the mass ratio of the coupling agent: anhydrous ethanol: deionized water is 10:10:1; In the step of preparing the nanoparticle dispersion, the nanoparticles account for 20% of the mass of the dispersion.
[0021] Preferably, in the step of preparing the silane coupling agent hydrolyzate, the temperature is heated to 40° C.-60° C. in a constant temperature water bath, and the stirring time is 2-4 hours.
[0022] In the preparation step of Solution A, stir at room temperature for 5-10 minutes; In the preparation step of Solution B, stir at room temperature for 10-30 minutes; In the preparation step of the mixed emulsion, liquid A and liquid B are mixed and stirred at room temperature for 10-30 minutes; after adding the coupling agent hydrolyzate, the mixture is stirred at room temperature for 30-60 minutes; the nanoparticle dispersion is added and the mixture is stirred at room temperature for 24 hours; In the coating curing step, the curing treatment includes placing it at room temperature for 10 minutes, pre-curing it in a 100°C oven for 30 minutes, and curing it in a 150-180°C oven for 2-3 hours; In the step of preparing the nanoparticle dispersion, the particle size of the particles is less than 10 nanometers.
[0023] The invention discloses an application of a super-hard, wear-resistant and anti-fouling composite coating in architectural decoration, electronic equipment, mechanical manufacturing or optical devices.
[0024] Therefore, the present invention adopts the above-mentioned preparation method and application of a superhard wear-resistant and antifouling composite coating, which has the following significant advantages in terms of hardness, wear resistance and scratch resistance, making it a low-cost option: Wear resistance: The coating has good mechanical strength and wear resistance, and can maintain its integrity during long-term use. This makes it widely used in applications requiring wear resistance, such as mechanical parts and tool surfaces.
[0025] Low cost: Compared to other high-performance coating materials, such as fluorocarbon coatings or ceramic coatings, organic-inorganic hybrid coatings have low manufacturing costs and relatively simple application processes. This makes silicone coatings economically advantageous in many applications that require large-area coating or large-scale production.
[0026] This technical solution, through the coupling of coupling agents, physical reinforcement of nanoparticles, curing and crosslinking of PETA, and flexible adjustment of silicone oil, constructs a "rigid and flexible" organic-inorganic hybrid network, effectively resolving the conflicts between hardness, wear resistance, adhesion, and processability faced by traditional coatings. Its design balances performance requirements with industrial feasibility, making it suitable for multiple high-value-added sectors such as automotive, electronics, and machinery manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a physical picture of the finished mixed emulsion; Figure 2 This is a physical picture of the coating sample; Figure 3 This is a test diagram of the coating's wear resistance; Figure 4 This is the test result of water contact angle of coating. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is further described below with reference to the accompanying drawings and embodiments.
[0029] Unless otherwise defined, technical or scientific terms used in the present invention shall have the same meaning as commonly understood by one of ordinary skill in the art to which the present invention belongs.
[0030] Example 1
[0031] A superhard, wear-resistant and antifouling composite coating comprises gamma-aminopropyltriethoxysilane, deionized water, anhydrous ethanol, amino silicone oil, hydroxy silicone oil, glycerol, pentaerythritol triacrylate, propylene glycol methyl ether acetate and nano zirconium dioxide dispersion.
[0032] Among them, the silane coupling agent is mixed with anhydrous ethanol and deionized water to be hydrolyzed and react with water to form silanol (Si-OH); Hydroxyl silicone oil, amino silicone oil, and glycerol are physically mixed. Glycerol is primarily used to enhance the dispersibility of subsequent nanoparticles and emulsions. Amino silicone oil reacts with the silane coupling agent hydrolyzate, and the hydroxyl groups in hydroxy silicone oil enhance molecular polarity. The silicone oil also provides antifouling properties to the coating.
[0033] Pentaerythritol triacrylate (PETA), anhydrous ethanol and propylene glycol methyl ether acetate (PMA) are physically mixed. PETA may not be completely soluble in anhydrous ethanol, but it is usually well soluble in PMA. When mixing the three, ensure that the solution does not become turbid, stratified or precipitated. The presence of PMA usually helps to dissolve PETA.
[0034] Slowly add liquid A to liquid B and mix well. Adding too quickly will cause a violent reaction and make the emulsion turbid or even gel.
[0035] After mixing liquid A and liquid B, add the silane coupling agent hydrolyzate and stir. If the addition is too fast, the reaction will be violent and will cause gelation.
[0036] Finally, the nano zirconium dioxide dispersion was slowly added to obtain a white uniform mixed emulsion; The mixed emulsion is applied to the surface of the pretreated substrate and cured to obtain a coating.
[0037] A clean glass surface has numerous exposed silanol (Si-OH) groups. The oxygen on the silanol groups nucleophilically replaces the silicon on the APTES, removing a portion of methanol to form a Si-O-Si bond, the primary method for silane coupling agents to form covalent bonds with surfaces. The amino groups then undergo a Michael addition reaction with the double bonds in PETA. Through the coupling of APTES, the physical reinforcement of nano-zirconium dioxide particles, the curing and cross-linking of PETA, and the flexible adjustment of silicone oil, a "rigid and flexible" organic-inorganic hybrid network is constructed, achieving enhanced wear resistance.
[0038] Preferably, the organic-inorganic hybrid coating provided in this embodiment includes 30-80 parts by weight of γ-aminopropyltriethoxysilane, 3-10 parts by weight of deionized water, 100-300 parts by weight of anhydrous ethanol, 5-50 parts by weight of aminosilicone oil, 1-30 parts by weight of hydroxysilicone oil, 1-20 parts by weight of glycerol, 200-500 parts by weight of pentaerythritol triacrylate, 50-200 parts by weight of propylene glycol methyl ether acetate, and 20-200 parts by weight of a nano-zirconium dioxide dispersion. Experiments in this embodiment also determined that the composition ratio with optimal coating performance is (6g PETA, 2g PMA, 2g anhydrous ethanol, 0.5g aminosilicone oil, 0.3g hydroxysilicone oil, 0.2g glycerol, 2.4g KH550 hydrolyzed solution, and 2g nano-zirconium dioxide dispersion). The specific amount used per part by weight is determined based on the total amount of coating required.
[0039] A method for preparing a superhard, wear-resistant, and antifouling composite coating comprises the following steps: Preparation of silane coupling agent hydrolyzate: Mix the silane coupling agent and anhydrous ethanol, add deionized water in an amount equivalent to 10% of the silane coupling agent, place in a constant temperature water bath at 40°C-60°C and stir for 2-4 hours to obtain the silane coupling agent hydrolyzate; Preparation of Liquid A: Mix hydroxy silicone oil, amino silicone oil, and glycerol in a mass ratio of 3:5:2 and stir at room temperature for 5-10 minutes to form a uniform mixture of Liquid A; Preparation of nano zirconium dioxide dispersion: Disperse zirconium dioxide particles with a particle size of less than 10 nanometers in an aqueous solution at a solid content of 20% to prepare a nano zirconium dioxide dispersion; Preparation of Liquid B: Mix pentaerythritol triacrylate, anhydrous ethanol, and propylene glycol methyl ether acetate in a mass ratio of 3:1:1, and stir at room temperature for 10-30 minutes to form a uniform mixture of Liquid B; Preparation of mixed emulsion: Slowly add liquid A into liquid B and mix evenly. After stirring at room temperature for 10-30 minutes, slowly add silane coupling agent hydrolyzate and stir at room temperature for 30-60 minutes. Finally, slowly add nano zirconium dioxide dispersion and continue stirring for 24 hours to obtain a white uniform mixed emulsion. Coating curing: Apply the mixed emulsion to the surface of the pretreated dry substrate (such as glass, metal, wood, ceramic, etc.) by spraying, scraping, spin coating or dipping. After leaving it at room temperature for 10 minutes, put it in a 100℃ oven for pre-curing for 30 minutes, and then cure it in a 150-180℃ oven for 2-3 hours.
[0040] Example 2
[0041] A method for preparing a superhard, wear-resistant, and antifouling composite coating, the specific process is as follows: (1) First, 5g of KH-550 and 5g of anhydrous ethanol were mixed evenly, and then 0.5g of deionized water was added and mixed evenly. The mixture was hydrolyzed at a constant temperature of 60°C for 4 hours to obtain a hydrolyzed solution; (2) Weigh 2.4 g of the hydrolyzate, 6 g of PETA, 2 g of anhydrous ethanol, 2 g of PMA, 0.5 g of amino silicone oil, 0.3 g of hydroxy silicone oil, 0.2 g of glycerol, and 1 g of nano zirconium dioxide dispersion, mix and stir for 24 h to fully react to obtain a mixture; (3) Finally, the above mixture was coated on the surface of the substrate, placed at room temperature for 10 minutes, pre-cured at 100°C for 30 minutes, and cured at 180°C for 2 hours to obtain a coating.
[0042] Example 3
[0043] A method for preparing a superhard, wear-resistant, and antifouling composite coating, the specific process is as follows: (1) First, 5g of KH-550 and 5g of anhydrous ethanol were mixed evenly, and then 0.5g of deionized water was added and mixed evenly. The mixture was hydrolyzed at a constant temperature of 60°C for 4 hours to obtain a hydrolyzed solution; (2) Weigh 2.4 g of the hydrolyzate, 6 g of PETA, 2 g of anhydrous ethanol, 2 g of PMA, 0.3 g of amino silicone oil, 0.3 g of hydroxy silicone oil, 0.2 g of glycerol, and 2 g of nano zirconium dioxide dispersion, mix and stir for 24 h to fully react to obtain a mixture; (3) Finally, the above mixture was coated on the surface of the substrate, placed at room temperature for 10 minutes, pre-cured at 100°C for 30 minutes, and cured at 180°C for 2 hours to obtain a coating.
[0044] Example 4
[0045] A method for preparing a superhard, wear-resistant, and antifouling composite coating, the specific process is as follows: (1) First, 5g of KH-550 and 5g of anhydrous ethanol were mixed evenly, and then 0.5g of deionized water was added and mixed evenly. The mixture was hydrolyzed at a constant temperature of 60°C for 4 hours to obtain a hydrolyzed solution; (2) Weigh 2.4 g of the hydrolyzate, 4 g of PETA, 2 g of anhydrous ethanol, 2 g of PMA, 0.5 g of amino silicone oil, 0.3 g of hydroxy silicone oil, 0.2 g of glycerol, and 2 g of nano zirconium dioxide dispersion, mix and stir for 24 h to fully react to obtain a mixture; (3) Finally, the above mixture was coated on the surface of the substrate, placed at room temperature for 10 minutes, pre-cured at 100°C for 30 minutes, and cured at 180°C for 2 hours to obtain a coating.
[0046] Example 5
[0047] A method for preparing a superhard, wear-resistant, and antifouling composite coating, the specific process is as follows: (1) First, 5g of KH-550 and 5g of anhydrous ethanol were mixed evenly, and then 0.5g of deionized water was added and mixed evenly. The mixture was hydrolyzed at a constant temperature of 60°C for 4 hours to obtain a hydrolyzed solution; (2) Weigh 2.0 g of the hydrolyzate, 6 g of PETA, 2 g of anhydrous ethanol, 2 g of PMA, 0.5 g of amino silicone oil, 0.3 g of hydroxy silicone oil, 0.2 g of glycerol, and 2 g of nano zirconium dioxide dispersion, mix and stir for 24 h to fully react to obtain a mixture; (3) Finally, the above mixture was coated on the surface of the substrate, placed at room temperature for 10 minutes, pre-cured at 100°C for 30 minutes, and cured at 180°C for 2 hours to obtain a coating.
[0048] Example 6
[0049] A method for preparing a superhard, wear-resistant, and antifouling composite coating, the specific process is as follows: (1) First, 5g of KH-550 and 5g of anhydrous ethanol were mixed evenly, and then 0.5g of deionized water was added and mixed evenly. The mixture was hydrolyzed at a constant temperature of 60°C for 4 hours to obtain a hydrolyzed solution; (2) Weigh 2.0 g of the hydrolyzate, 6 g of PETA, 2 g of anhydrous ethanol, 2 g of PMA, 0.5 g of amino silicone oil, 0.3 g of hydroxy silicone oil, 0.2 g of glycerol, and 2 g of nano zirconium dioxide dispersion, mix and stir for 24 h to fully react to obtain a mixture; (3) Finally, the above mixture was coated on the surface of the substrate, placed at room temperature for 10 minutes, pre-cured at 100°C for 30 minutes, and cured at 150°C for 2 hours to obtain a coating.
[0050] Example 7
[0051] A method for preparing a superhard, wear-resistant, and antifouling composite coating, the specific process is as follows: (1) First, 5g of KH-550 and 5g of anhydrous ethanol were mixed evenly, and then 0.5g of deionized water was added and mixed evenly. The mixture was hydrolyzed at a constant temperature of 60°C for 4 hours to obtain a hydrolyzed solution; (2) Weigh 2.0 g of the hydrolyzate, 6 g of PETA, 2 g of anhydrous ethanol, 2 g of PMA, 0.5 g of amino silicone oil, 0.3 g of hydroxy silicone oil, and 0.2 g of glycerol, and mix them. Stir for 24 h to allow for sufficient reaction to obtain a mixture. (3) Finally, the above mixture was coated on the surface of the substrate, placed at room temperature for 10 minutes, pre-cured at 100°C for 30 minutes, and cured at 180°C for 2 hours to obtain a coating.
[0052] Example 8
[0053] A method for preparing a superhard, wear-resistant, and antifouling composite coating, the specific process is as follows: (1) First, 5g of KH-550 and 5g of anhydrous ethanol were mixed evenly, and then 0.5g of deionized water was added and mixed evenly. The mixture was hydrolyzed at a constant temperature of 60°C for 4 hours to obtain a hydrolyzed solution; (2) Weigh 6 g of PETA, 2 g of anhydrous ethanol, 2 g of PMA, 0.5 g of amino silicone oil, 0.3 g of hydroxy silicone oil, 0.2 g of glycerol, and 2 g of nano zirconium dioxide dispersion, mix them, and stir for 24 h to fully react to obtain a mixture; (3) Finally, the above mixture was coated on the surface of the substrate, placed at room temperature for 10 minutes, pre-cured at 100°C for 30 minutes, and cured at 180°C for 2 hours to obtain a coating.
[0054] Embodiment 9
[0055] A method for preparing a superhard, wear-resistant, and antifouling composite coating, the specific process is as follows: (1) First, 5g of KH-550 and 5g of anhydrous ethanol were mixed evenly, and then 0.5g of deionized water was added and mixed evenly. The mixture was hydrolyzed at a constant temperature of 60°C for 4 hours to obtain a hydrolyzed solution; (2) Weigh 2.0 g of the hydrolyzate, 2 g of anhydrous ethanol, 2 g of PMA, 0.5 g of amino silicone oil, 0.3 g of hydroxy silicone oil, 0.2 g of glycerol, and 2 g of nano zirconium dioxide dispersion, mix them, and stir for 24 h to fully react to obtain a mixture; (3) Finally, the above mixture was coated on the surface of the substrate, placed at room temperature for 10 minutes, pre-cured at 100°C for 30 minutes, and cured at 180°C for 2 hours to obtain a coating.
[0056] Example 10
[0057] A method for preparing a superhard, wear-resistant, and antifouling composite coating, the specific process is as follows: (1) First, 5g of KH-550 and 5g of anhydrous ethanol were mixed evenly, and then 0.5g of deionized water was added and mixed evenly. The mixture was hydrolyzed at a constant temperature of 60°C for 4 hours to obtain a hydrolyzed solution; (2) Weigh 2.0 g of the hydrolyzate, 6 g of PETA, 2 g of anhydrous ethanol, 2 g of PMA, 0.3 g of hydroxy silicone oil, 0.2 g of glycerol, and 2 g of nano zirconium dioxide dispersion, mix them, and stir for 24 h to fully react to obtain a mixture; (3) Finally, the above mixture was coated on the surface of the substrate, placed at room temperature for 10 minutes, pre-cured at 100°C for 30 minutes, and cured at 180°C for 2 hours to obtain a coating.
[0058] The substrate in Examples 1 to 10 is preferably a glass substrate.
[0059] Comparing Example 1 with Examples 2, 5, 7, and 8, it can be seen that the amount of added nanoparticles and the amount of hydrolyzate will affect the hardness and wear resistance of the coating to a certain extent. The coupling after hydrolysis of the coupling agent and the physical strengthening of the nanoparticles further enhance the hardness of the hybrid coating.
[0060] By comparing Example 1 with Examples 3, 4, 9 and 10, it can be seen that the addition of an appropriate amount of amino silicone oil and pentaerythritol triacrylate helps to improve the contact angle of the coating through the construction of the surface silicone oil, and the Michael addition reaction between the amino group and the double bond in PETA will affect the construction of the anti-fouling performance of the coating to a certain extent.
[0061] By comparing Example 1 with Example 6, it can be seen that the coating hardness is insufficient when the curing temperature is low, and the coating hardness increases as the curing temperature increases.
[0062] Figure 1 The mixed emulsion prepared by the method of Example 1; Figure 2 The coating sample is obtained by coating the mixed emulsion on the substrate; Figure 3 Under the load of 500 grams, the coating was scratched 10,000 times with #0000 steel wool, and there was no scratch and little loss of quality. The coating has excellent wear resistance.
[0063] Figure 4 The measured water contact angle of the coating is L:103.362, R:100.596, CA:101.979, and the tilt angle is 0.00. Its water contact angle is greater than 100°, and it has hydrophobic properties; graffiti on the coating with an oil pen can be quickly erased, and it has anti-graffiti properties; the coating has a high hardness, which can reach 9H; under a load of 500 grams, the coating has no scratches and little mass loss after 10,000 cycles of scratching with #0000 steel wool, and the coating has good wear resistance.
[0064] Therefore, the present invention adopts the preparation method and application of the above-mentioned super-hard wear-resistant and anti-fouling composite coating, which has the advantages of high hardness, wear resistance, scratch resistance and low cost.
[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the same. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solutions of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A super-hard, wear-resistant and anti-fouling composite coating, characterized in that: include 30-80 parts by weight of coupling agent 3-10 parts by weight of deionized water 100-300 parts by weight of anhydrous ethanol 5-50 parts by weight of amino silicone oil 1-30 parts by weight of hydroxy silicone oil 1-20 parts by weight of glycerol Pentaerythritol triacrylate 200-500 parts by weight Propylene glycol methyl ether acetate 50-200 parts by weight 20-200 parts by weight of nanoparticle dispersion.
2. The superhard, wear-resistant and antifouling composite coating according to claim 1, characterized in that: The mass ratio of hydroxy silicone oil, amino silicone oil and glycerol is 3:5:2; The mass ratio of pentaerythritol triacrylate, anhydrous ethanol and propylene glycol methyl ether acetate is 3:1:
1.
3. The superhard, wear-resistant and antifouling composite coating according to claim 1, characterized in that: The coupling agent is one or more of a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, and a zirconate coupling agent.
4. The superhard, wear-resistant and antifouling composite coating according to claim 1, characterized in that: The coupling agent is one or more of γ-aminopropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltriethoxysilane, tetrabutyl titanate, bis(ethyl acetoacetate)di-n-butoxy titanate, aluminum triacetylacetonate, (ethyl acetoacetate)diisopropoxyaluminate, tetrakis(triethanolamine)zirconium, and alkoxytris(p-aminophenoxy)zirconate.
5. The superhard, wear-resistant and antifouling composite coating according to claim 1, characterized in that: The nanoparticle dispersion is one of zirconium oxide, aluminum oxide, titanium oxide and silicon oxide.
6. A method for preparing a superhard, wear-resistant and antifouling composite coating, characterized in that: The following steps are involved: Preparation of coupling agent hydrolyzate: Mix the coupling agent and anhydrous ethanol in proportion, add deionized water, place in a constant temperature water bath and stir to obtain coupling agent hydrolyzate; Preparation of Liquid A: Mix hydroxy silicone oil, amino silicone oil and glycerol and stir to form a uniform mixture of Liquid A; Preparation of nanoparticle dispersion: dispersing nanoparticles in an aqueous solution to prepare a nanoparticle dispersion; Preparation of Liquid B: Pentaerythritol triacrylate, anhydrous ethanol and propylene glycol methyl ether acetate were mixed and stirred to form a uniform mixture of Liquid B; Preparation of mixed emulsion: slowly add liquid A to liquid B and mix evenly, stir, slowly add coupling agent hydrolyzate and stir, and finally slowly add nanoparticle dispersion and continue stirring to obtain a uniform mixed emulsion; Coating curing: The mixed emulsion is applied to the surface of the pretreated substrate and cured to obtain a coating.
7. The method for preparing a superhard, wear-resistant and antifouling composite coating according to claim 6, characterized in that: Substrates include glass, metal, wood or ceramic.
8. The method for preparing a superhard, wear-resistant and antifouling composite coating according to claim 6, characterized in that: In the step of preparing the coupling agent hydrolyzate, a mixed solution of the coupling agent and deionized water is prepared, wherein the deionized water accounts for 10% of the mass of the coupling agent, and the mass ratio of the coupling agent: anhydrous ethanol: deionized water is 10:10:1; In the step of preparing the nanoparticle dispersion, the nanoparticles account for 20% of the mass of the dispersion.
9. The method for preparing a superhard, wear-resistant and antifouling composite coating according to claim 6, characterized in that: In the preparation step of the silane coupling agent hydrolyzate, the temperature is heated to 40° C.-60° C. in a constant temperature water bath and the stirring time is 2-4 hours; In the preparation step of Solution A, stir at room temperature for 5-10 minutes; In the preparation step of Solution B, stir at room temperature for 10-30 minutes; In the preparation step of the mixed emulsion, liquid A and liquid B are mixed and stirred at room temperature for 10-30 minutes; after adding the coupling agent hydrolyzate, the mixture is stirred at room temperature for 30-60 minutes; the nanoparticle dispersion is added and the mixture is stirred at room temperature for 24 hours; In the coating curing step, the curing treatment includes placing it at room temperature for 10 minutes, pre-curing it in a 100°C oven for 30 minutes, and curing it in a 150-180°C oven for 2-3 hours; In the step of preparing the nanoparticle dispersion, the particle size of the particles is less than 10 nanometers.
10. Use of the superhard, wear-resistant and antifouling composite coating according to claim 1 in architectural decoration, electronic equipment, mechanical manufacturing or optical devices.
Citation Information
Patent Citations
High-hardness, anti-adhesion and light-transmitting organic silicon coating material and preparation method thereof
CN114854236A
Transparent hydrophobic and oleophobic coating, preparation method thereof and formed transparent hydrophobic and oleophobic coating
CN116694115A
Preparation method of high-hardness organic silicon coating
CN116694120A